Hybridity in Spanish culture - Tajes, María P., 1970-; Knudson-Vilaseca, Emily; Tobin Stanley, Maureen (Cambridge Scholars Pub., 2011)
Hybridity in Spanish Culture is an anthology that explores hybridity in select works from the dawn of Imperial Spain to the twenty-first century. The phenomenon of hybridity has been pervasive throughout Spanish history. The hybrid literary and visual texts studied in this volume-ranging from aljamiado writings and the legacy from the convivencia to contemporary immigration narratives-blur or erase purportedly fixed boundaries: between history and fiction, story and History, nationality and t ...